The service-seeking profiles of youth reporting a legal mandate or perceived coercion for substance use treatment. (March 2019) - Bath, Karanpreet; Hawke, Lisa D.; Skilling, Tracey; Chaim, Gloria; Henderson, Joanna
Abstract: Introduction: There is paucity of research on treatment-related coercion in youth: most research focuses on adult populations and legally mandated treatment. This study aims to examine the service-seeking profiles of youth with substance misuse issues who report a legal mandate or perceived coercion to enter treatment. Methods: Differences between youth who were legally mandated and not legally mandated, and differences between youth reporting high and low perceived coercion, were examined for demographic characteristics, mental health and substance use profiles, motivation, and readiness to change. Results: Compared to participants reporting low perceived coercion, those experiencing high perceived coercion reported more substance use problems, greater mental health needs, and greater external and introjected motivation. Legally mandated youth reported fewer mental health issues, lower identified motivation, and greater readiness to change than those reporting no legal mandate. Discussion: Many youth who present for substance use services report experiencing a sense of coercion, which suggests the potential importance of considering youth-centered strategies for involving youth in treatment planning and the development of treatment goals. Youth seeking treatment also have multiple intersecting needs which may benefit from a collaborative and integrative approach. Highlights: Limited research on coercion in youth beyond the legal system. Study compares legally vs not legally mandated, and high vs low perceived coercion. 14.0% of sample was legally mandated; 31.7% reported high perceived coercion. Less substance use and mental health issues in legally mandated youth. Perceiving high coercion was related to more substance use and mental health issues.